O SinTUFRJ e a formação humana de servidores técnico-administrativos em educação da UFRJ (1993-2020) - Jesus, Henrique de Oliveira Santos Vieira de (2021)
The aim of this research is to verify if and how the Union of Workers in Education of the Federal University of Rio de Janeiro (Sintufrj, its acronym in Portuguese) contributes to the formation of unionized workers, from 1993 to 2020. The qualitative research uses the dialectical method. Documentary research was carried out, which focused on newspapers, reports, booklets, public notices, and the presentation of programs available on the Sintufrj website, in addition to interviews with nine unionized technical-administrative workers at UFRJ. The theoretical framework was based on the Marxist tradition of discussions about work and its repercussions on the formation of human beings, especially considering the offer of activities by unions for their members. The main results of the research indicate that Sintufrj’s actions did not presuppose the total, complete and multilateral development of the faculties and productive forces. Such actions focused on technical improvement and bodily conditions so that unionized workers could better perform the tasks of their work at the university. Sintufrj’s initiatives for formation seemed more focused on satisfying the immediate needs of workers, not necessarily opposing the neoliberal project, which seeks to strengthen the primacy of capital and pulverize the defense of collective interests by Sintufrj. Among the main conclusions, it is worth noting that Sintufrj should develop initiatives aimed at the emancipation of the worker in intellectual terms so that he/she understands the operation of the socio-metabolic order of capital, as well as technological terms – so that he/she understands how material and human resources are distributed – and bodily terms, so that he/she becomes aware of how the system controls his/her own bodies.